KONSEPTUALISASI METAFORA FEMINIS DALAM MEDIA SOSIAL TWITTER: ANALISIS SEMANTIK KOGNITIF (Conceptualization of Feminist Metaphors in Social Media Twitter: Cognitive Semantic Analysis) - Fatim, Al Lastu Nurul; Al Anshory, Abdul Muntaqim (Kantor Bahasa Provinsi Sulawesi Tenggara, 2023)
There are several places in which feminist expressions can be found, including on social media platforms like Twitter. A variety can write arguments, opinions, and ideas communicated through Twitter tweets. This study aims to discover conceptual metaphors for feminist expressions that influencer Iim Fahima Jachja posted on Twitter. The listen and record method was employed to collect data. The data analysis is based on Lakoff & Johnson's (2003) theory of conceptual metaphors as well as Croft & Cruse's (2004) image schemes theory. There were 11 conceptual metaphorical data points were found, split into five structural metaphors, two orientational metaphors, and four ontological metaphors. Meanwhile, three types of schemes may be discovered in the image schemes: force schemes, identity schemes, and existence schemes. Ungkapan feminis dapat ditemukan pada berbagai wacana, termasuk media sosial seperti twitter. Berbagai tokoh dapat menuliskan ujarannya mulai dari argumen, pendapat, dan ide yang dituangkan melalui twitter. Tujuan penelitian ini dimaksudkan untuk mengidentifikasi metafora konseptual pada ungkapan feminis yang terdapat pada twitter dari influencer Iim Fahima Jachja. Metode simak dan cata digunakan sebagai pengumpulan data. Analisis datanya didasarkan pada metafora konseptual Lakoff & Johnson (2003) dan teori skema citra Croft & Cruse (2004). Ditemukan 11 data metafora konseptual yang terbagi menjadi: a) 5 metafora struktural; b) 2 metafora orientasional; c) 4 metafora ontologis. Sedangkan, pada skema citra terdapat 3 jenis skema yang ditemukan yaitu, skema kekuatan, skema identitas, dan skema eksistensi.